2018
DOI: 10.1002/ange.201801538
|View full text |Cite
|
Sign up to set email alerts
|

An Amorphous Noble‐Metal‐Free Electrocatalyst that Enables Nitrogen Fixation under Ambient Conditions

Abstract: N 2 fixation by the electrocatalytic nitrogen reduction reaction (NRR) under ambient conditions is regarded as ap otential approach to achieve NH 3 production, which still heavily relies on the Haber-Boschp rocess at the cost of huge energy and massive production of CO 2 .Anoble-metal-free Bi 4 V 2 O 11 /CeO 2 hybrid with an amorphous phase (BVC-A) is used as the cathode for electrocatalytic NRR. The amorphous Bi 4 V 2 O 11 contains significant defects,w hichp lay ar ole as active sites.The CeO 2 not only serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(69 citation statements)
references
References 49 publications
(82 reference statements)
2
67
0
Order By: Relevance
“…Therefore, rational design of the catalyst surfacem ust result in an optimum Na tom binding strength. [46] It has been suggested that the presence of OVs induces modification of the electronic structure of layered double-hydroxide nanosheets and amorphous Bi 4 V 2 O 11 , [47,48] which impactst heir electron transfer to adsorbates,a nd thereby contributes to the N 2 activation and N 2 cleavage. The introduction of more surface OVs on the hematite nanostructure may lead to more active sites for N 2 reduction.R ecently,t he defects were also revisited to act as active centers for other electrocatalytic processes (e.g.,o xygen reduction/evolution reaction).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, rational design of the catalyst surfacem ust result in an optimum Na tom binding strength. [46] It has been suggested that the presence of OVs induces modification of the electronic structure of layered double-hydroxide nanosheets and amorphous Bi 4 V 2 O 11 , [47,48] which impactst heir electron transfer to adsorbates,a nd thereby contributes to the N 2 activation and N 2 cleavage. The introduction of more surface OVs on the hematite nanostructure may lead to more active sites for N 2 reduction.R ecently,t he defects were also revisited to act as active centers for other electrocatalytic processes (e.g.,o xygen reduction/evolution reaction).…”
Section: Resultsmentioning
confidence: 99%
“…[45] On the other hand, theoretical studies revealed that OVs could facilitate N 2 adsorption and N 2 activation by elongating the NNt ripleb ond. [46] It has been suggested that the presence of OVs induces modification of the electronic structure of layered double-hydroxide nanosheets and amorphous Bi 4 V 2 O 11 , [47,48] which impactst heir electron transfer to adsorbates,a nd thereby contributes to the N 2 activation and N 2 cleavage. Therefore, it is reasonable to infer that ah igherc oncentration of OVs on the hematite surface is criticaltothe electrocatalytic reduction of N 2 to NH 3 ,a lthough there is still al ack of mechanistic insights.…”
Section: Resultsmentioning
confidence: 99%
“…Before NRR test, Nafion membrane was protonated following the previous reports [6] (more detailed description can be found in the Supporting Information). The electrochemical NRR tests were performed using an H-cell system that was isolated by Nafion 211 membrane.…”
Section: Methodsmentioning
confidence: 99%
“…[49] All these results confirmed the co-existence of anatase TiO 2 and Ti 3 C 2 T x nanosheets in the astreated samples, which was defined as TiO 2 /Ti 3 C 2 T x accordingly. [6,25] The morphologies and structures of the Ti 3 C 2 T x and TiO 2 / Ti 3 C 2 T x were characterized by the transmission electron microscopy (TEM) and scanning electron microscopy (SEM) techniques, respectively. Figure 1E-G shows a comparison of the XPS analysis of Ti, C, and O from the two samples.…”
mentioning
confidence: 99%
“…Previous studies have proved that noble‐metal based catalysts are efficient N 2 reduction reaction (NRR) electrocatalysts, but their large‐scale uses are severely limited by the high cost and rareness. Considerable recent attention has thus focused on earth‐abundant transition metal‐based alternatives to effectively catalyze the NRR . Nevertheless, metal ions may be released from such catalysts, leading to environmental pollution.…”
Section: Figurementioning
confidence: 99%